PEDAGOGICAL TASKS OF SPEECH THERAPIST AND PARENT COOPERATION IN ELIMINATING SPEECH DEFECTS (American Journal of Interdisciplinary Research and Development, 2023)
Working with parents is a complex and important part of the activity of a speech and language pathologist. It includes the interaction of parents and educators, pedagogues in creating and raising a child.